Ribonucleic acids from barley leaves - Srivastava, B. I. Sahai (1965)
1. The total RNA and the RNA present in 27000g pellet (probably composed of chloroplasts, nuclei and mitochondria) and in 27000g supernatant (probably composed of microsomes and soluble proteins) fractions (separated by centrifugation at 27000g of a leaf homogenate prepared in 0·5m-sucrose–0·02m-tris–HCl, pH7·6) of barley leaves were extracted by phenol–sodium lauryl sulphate and their elution profiles on Sephadex G-200 and on ECTEOLA-cellulose anion-exchanger were examined and their nucleotide compositions and the melting curves were determined. 2. The pellet and the supernatant fractions contained respectively about 55% and 20% of the total RNA, whereas 25% of the total RNA was lost during homogenization of the leaf tissue with sucrose–buffer. 3. The total RNA or the RNA from pellet or supernatant fractions, which by its behaviour on Sephadex G-200 columns was found to be predominantly of high molecular weight (i.e. of ribosomal origin), produced about 13 peaks on ECTEOLA-cellulose columns. The RNA species in the pellet and supernatant fractions probably resembled each other in molecular size or secondary structure or both. However, they were present in relatively different amounts in these fractions. 4. The T(m) (i.e. the temperature at which 50% of the maximal increase in extinction had occurred) of total RNA and of RNA from pellet fraction was 64·5° whereas T(m) of RNA from the supernatant fraction was 73°. The total RNA and the RNA from pellet fraction also resembled each other in nucleotide composition, and the RNA from the supernatant fraction in accordance with its high T(m) had a high GMP+CMP content.